Beyond Codes: The Role of the Indonesian Civil Service Commission in Promoting Ethics within Indonesia's Civil Service - Fitriana Dewi, Ari (Indonesian Association for Public Administration (IAPA), 2024)
This research studies an Indonesian integrity body with key roles in promoting ethical conduct across government agencies. The key research question is: How has the Indonesian Civil Service Commission played a role in ethics management within Indonesia's civil service? This research uses a qualitative case study by analysing documents to understand how a particular organisation employed its work in promoting ethics. This research finds that despite its intended role as an enforcement agency of ethics rules, the ICSC rolled out various mechanisms for translating its role into practice. The ICSC has implemented a combination of compliance and value-based approach that encourages individual civil servants to adhere to ethics codes while enabling the human resource unit to champion and promote ethics within government agencies, implementing ethics beyond adherence to ethical codes and cultivating ethical culture.